Intradural Extramedullary Spinal Sarcoidosis Mimicking Meningioma. (5th August 2019) - Ishiwata, Sho; Iizuka, Yoichi; Mieda, Tokue; Hirato, Junko; Koshi, Hiromi; Kakuta, Yohei; Honda, Akira; Sonoda, Hiroyuki; Tajika, Tsuyoshi; Chikuda, Hirotaka
Abstract : Background . Spinal sarcoidosis is a rare subgroup of neurosarcoidosis. Although most sarcoid lesions develop in the intramedullary compartment, intradural extramedullary (IDEM) spinal sarcoidosis is an extremely rare entity. Case Presentation . We herein report a case of IDEM spinal sarcoidosis mimicking a meningioma. A 32-year-old man presented to the hospital with clumsy hands and was unable to walk without assistance. Magnetic resonance imaging (MRI) of the cervical spine revealed a dural tail sign that is common in meningiomas. The patient underwent gross total resection. The pathological findings consisted with a sarcoid leision of the spinal cord. The patient's myelopathy recovered after surgery. Conclusions . Physicians should be alert for the possibility of IDEM sarcoidosis mimicking a meningioma in the differential diagnosis of IDEM spinal cord tumors.